A3 3 Clarkson’s Chernobyl Incident - Bentley, Bobby Majid; Lebidineuse, Leon Luc; McFahn, Ryan (Physics Special Topics, 2023)
This paper investigates the effectiveness of Jeremy Clarkson’s method of opening his car boot to run out of fuel before arriving in Chernobyl. We use air resistance and power equations to find that with the boot open, the car uses 6.83 l/hr when travelling at 110 km/hr. This is an approximate 85% increase to the normal efficiency of the car.